They did not even ask for it! On Women’s Suffrage in the Kingdom of Serbs, Croats and Slovenes - Drakić, Gordana M (Zbornik radova Pravnog fakulteta u Novom Sadu, 2019)
Women in the Kingdom of Serbs, Croats and Slovenes did not have the right to vote. Women’s suffrage was not prescribed by Vidovdan Constitution. Regarding women’s voting rights, the Constitution only contained a certain provision that stipulated that women’s suffrage would be resolved by a special law. The paper deals with efforts put from feminist’s organizations in the Yugoslav Kingdom in order to achieve suffrage for women. Speeches that were held in the Temporary National Assembly by MPs who advocated the idea of women’s voting rights are presented in the paper. The paper also presents the discussions that were conducted in the Constitutional Assembly between deputies who were supporters and those who were opposed to the women’s suffrage, as well as those held during the parliamentary debate on the electoral law. The author points out the activity of women’s associations in the Kingdom of Serbs, Croats and Slovenes which fought for women’s suffrage and which advocated change of opinion that existed in the Yugoslav society of that time, that women should be spared from the inconvenience that political struggle implies, until they achieve the proper level of ability to engage in it. In addition, a brief overview of the evolution of the issue of women’s voting rights is given in the paper. It is also emphasized that women in the territory of Voivodina had the right to elect and to be elected during the election of representatives for the Great National Assembly which was held in Novi Sad in November 1918. Overall, the women’s issue was a matter of secondary significance in the Kingdom of Serbs, Croats and Slovenes, because there were many unresolved issues, such as national one, that occupied the attention both of the relevant state factors and the public.